A mixed methods analysis of cannabis use routines for chronic pain management - Kevin F. Boehnke; Laura Yakas; J. Ryan Scott; Melissa DeJonckheere; Evangelos Litinas; Suzanne Sisley; Daniel J. Clauw; David A. Williams; Jenna McAfee (BMC, 2022)
Abstract Background The wide heterogeneity of available cannabis products makes it difficult for physicians to appropriately guide patients. In the current study, our objective was to characterize naturalistic cannabis use routines and explore associations between routines and reported benefits from consuming cannabis. Methods We performed a mixed methods analysis of n=1087 cross-sectional survey responses from adults with self-reported chronic pain using cannabis for symptom management in the USA and Canada. First, we qualitatively analyzed responses to an open-ended question that assessed typical cannabis use routines, including administration routes, cannabinoid content, and timing. We then sub-grouped responses into categories based on inhalation (smoking, vaporizing) vs. non-inhalation (e.g., edibles). Finally, we investigated subgroups perceptions of how cannabis affected pain, overall health, and use of medications (e.g., substituting for opioids, benzodiazepines). Substitutions were treated as a count of medication classes, while responses for both pain and health were analyzed continuously, with − 2 indicating health declining a lot or pain increasing a lot and 2 indicating that health improved a lot or pain decreased a lot. Results Routines varied widely in terms of administration routes, cannabinoid content, and use timing. Overall, 18.8%, 36.2%, and 45% used non-inhalation, inhalation, and non-inhalation + inhalation routes, respectively. Those who used inhalation routes were younger (mean age 46.5 [inhalation] and 49.2 [non-inhalation + inhalation] vs. 56.3 [inhalation], F=36.1, p<0.001), while a higher proportion of those who used non-inhalation routes were female (72.5% non-inhalation vs. 48.3% inhalation and 65.3% non-inhalation + inhalation, X 2=59.6, p<0.001). THC-rich products were typically used at night, while CBD-rich products were more often used during the day. While all participants reported similarly decreased pain, participants using non-inhalation + inhalation administration routes reported larger improvements in health than the non-inhalation (mean difference = 0.32, 95% CI: 0.07-0.37, p<0.001) and inhalation subgroups (mean difference = 0.22, 95% CI: 0.07-0.37, p=0.001). Similarly, the non-inhalation + inhalation group had significantly more medication substitutions than those using non-inhalation (mean difference = 0.62, 95% CI: 0.33-0.90, p<0.001) and inhalation administration routes (mean difference = 0.45, 95% CI: 0.22-0.69, p<0.001), respectively. Conclusions Subgrouping medical cannabis patients based on administration route profile may provide useful categories for future studies examining the risks and benefits of medical cannabis.